THE EFFECT OF DRYING FOR THE BREAKING STRENGTH OF POLYAMIDE YARNS WHICH HAVA EXPERIENCED THE PRESERVATION OF JENGKOL BARK EXTRACT (Archidendronpaucifiorum) AND SALAM BARK EXTRACT (Syzygium polyanthum). - Murdani, Ade; ', Isnaniah; ', Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTAde Murdani@ymail.comThis research was conducted on July to September 2014, which is held in the Laboratory of fishing Gear Materials, Utilization of Water Resources, The Faculty of Fisheries and Marine Sciences, University of Riau. The purpose of this study was to know the effect of drying for the breaking strength of polyamide yarns which have experienced the preservation of jengkol bark extract and salam bark extract. This study used an experimental method by performing the experiments effect of drying outdoors directly in sunlight and in a room with aerated for breaking strength of yarns PA(polyamide) whinch heve experienced the preservation. The breaking strength of yarns that used jengkol and salam bark extract which were dried in the room are higher than the yarns in the outdoors with directly sunlight. The soaking of yarns by using jengkol bark extract resulted the better breaking strength of yarns than the yarns which were soaked by salam bark extract.Keyword : breaking strength, yarns polyamide, extracts, drying